Neuroprotective effect of regional carnitine on spinal cord ischemia-reperfusion injury - Rahman, A; Üstündag, B; Burma, O; Özercan, IH; Erol, FS (Oxford Univ Press Inc, 2001)
Objective: The purpose of this study was to investigate the effect of regional infusion of carnitine on spinal cord ischemia-reperfusion (IR) in rabbits. Methods: The 36 rabbits were divided into four equal groups, group I (sham operated, no I-R injury), group II (control, only IR), group III (I-R + intraaortic lactated Ringer's, LR, during aortic occlusion), group IV (I-R + LR plus 100 mg/kg carnitine). Spinal cord ischemia was induced by clamping the aorta both below the left renal artery and above the aortic bifurcation. The spinal cord function of all animals was assessed clinically 24 h after aortic declamping. Spinal cord samples were taken to measure the levels of tissue malondialdehyde (MDA) and to evaluate the histopathological changes. Results: We found significant increases in the levels of MDA in groups II and III compared with group I (P < 0.01), and elevation of MDA in group IV was insignificant. In group II, all animals (100%) were paraplegic with Tarlov's score of 0 and in group III, eight animals (88%) were paraplegic with Tarlov's score of 0 or 1. None of the animals (0%) from group IV was paraplegic. Histologic examination of spinal cords from group IV animals revealed that the appearance of the spinal cord was relatively preserved, whereas spinal cords from groups II and III had evidence of acute neuronal injury. Conclusion: The results suggest that regional infusion of carnitine during aortic clamping reduces spinal cord injury and prevents neurologic damage in rabbit spinal cord I-R model. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: carnitine; spinal cord; ischemia-reperfusion injury